Research on the internal mechanism and path of the new growth point of marine biological economy - Zhou, Jianlong; Li, Bin (Frontiers in Ecology and Evolution, 2022)
In order to explore how the marine economy can realize the new growth point of economic development, this study puts forward a research method based on the internal mechanism and path of the new growth point of marine economic development. This method recommends key technical problems and solutions based on the research method of the internal mechanism and path of developing new growth points, amphibious science that further integrates, ecological, and socialized theory and application and explores the internal mechanism and path of how the marine economy realizes the new growth points of economic development. The research shows that the research on the internal mechanism and path of developing new growth points has increased the marine economy by nearly 45%, deeply analyzes the internal relationship between coastal economic growth and marine pollution, the close relationship between marine resources development and marine economic growth, and briefly summarizes the marine economic growth path against the background of the adjustment and change of marine industrial structure.